Pelayanan Komprehensif Berkesinambungan dalam Program Penanggulangan HIV/AIDS di Kota Surakarta - Demartoto, Argyo; IES, Endang Gerilyawati; Sudibyo, Desiderius Priyo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2014)
Penelitian ini bertujuan untuk mengetahui karakteristik demografi, sosial, dan ekonomi ODHA; pengetahuan, sikap, dan perilaku stakeholders terhadap HIV/AIDS dan ODHA; dukungan dan pelayanan komprehensif berkesinambungan serta pengaruh stakeholders dalam program penanggulangan HIV/ AIDS di Kota Surakarta. Metode penelitian ini adalah eksploratif. Teknik pengambilan sampel dengan purposive sampling. Pengumpulan data dilakukan dengan observasi, indepth interview, Focus Group Discussion, dan dokumentasi. Teknik analisa data dengan model analisis interaktif. Hasil penelitian menunjukkan bahwa di Kota Surakarta pada umumnya ODHA berusia produktif, laki-laki, heteroseksual,bekerja sebagai karyawan, mempunyai masalah medis dan kultur sosial seperti mempunyai infeksi oportunistik, efek samping obat ARV, depresi, mengalami diskriminasi, stigma negatif, dikucilkan keluarga dan anggota masyarakat. Stakeholders pelayanan komprehensif berkesinambungan dalam penanggulangan HIV/AIDS di Kota Surakarta mempunyai pengetahuan tentang HIV/AIDS yang baik, sikap peduli dan bertindak responsif terhadap ODHA. Dukungan dan pelayanan komprehensif berkesinambungan di mulai dari saat menjalani test; pengadaan obat-obatan Antiretroviral (ARV); perlakuan yang etis dan tidak diskriminatif; pencegahan dan pengobatan infeksi oportunistik; terapi non medis dan Kelompok Dukungan Sebaya. Kata kunci : stakeholders, pelayanan komprehensif berkesinambungan, penanggulangan HIV/AIDS. ABSTRACT Continuous Comprehensive Care Program for HIV / AIDS in Surakarta; This research aimed to find out the demographic, social and economic characteristics of people with HIV/AIDS (ODHA); stakeholders’ knowledge, attitude, and behavior toward HIV/AIDS and people with HIV/AIDS; comprehensive and sustainable support and service, as well as the contribution of stakeholders to the HIV/AIDS management program in Surakarta City. The research method employed was an exploratory one. The sampling technique used was purposive sampling one. The data collection was conducted using observation, in-depth interview, Focus Group Discussion, and documentation. Technique of analyzing data used was an interactive model of analysis. The result of research showed that in Surakarta, generally people with HIV/AIDS were productive, female, heterosexual and working as employees, having medical problem and social culture such as developing opportunistic infection, ARV drug side effect, depression, discriminated, negative stigma, isolated by the family and society member. The stakeholders of sustainable and comprehensive service in dealing with HIV/AIDS in Surakarta City had good knowledge about HIV/AIDS, caring and responsiveness to the people with HIV/AIDS. A comprehensive and sustainable support and service started during undertaking test; antriretroviral (ARV) drugs procurement, ethical and non-discriminatory treatment; opportunistic infection prevention and treatment; non-medical therapy and Peer-Group Support. Keywords: stakeholders, comprehensive and sustainable service, HIV/AIDS management.